Long-Acting Injectable Antipsychotic Use in Patients with Schizophrenia and Criminal Justice System Encounters - Madhav P. Bhatta; Saroj Bista; Antoine C. El Khoury; Eric G. Hutzell; Neeta Tandon; Douglas Smith (Journal of Health Economics and Outcomes Research)
**Background:** Nonadherence to medication is prevalent in persons diagnosed with schizophrenia, thus increasing the likelihood of relapse, poor health outcomes, hospitalization, high treatment costs, and high rates of both violent and non-violent offenses.